A dynamical study of the chirally rotated Schrödinger functional in lattice QCD - Brida, Mattia Dalla (Trinity College (Dublin, Ireland). School of Mathematics, 2015)
In this work, we present first results from dynamical simulations of the chirally rotated Schrödinger functional (SF) in lattice QCD. More specifically, we discuss the determination of renormalization constants of quark-bilinears, and show evidence for the expected automatic 0(α) improvement of these determinations. After a short introduction on the topics of non-perturbative renormalization and improvement in lattice field theory, we recall the technical advantages of renormalization schemes based on the SF. We then motivate and discuss the lattice regularization of the SF with chirally rotated boundary conditions, and present details and tests on the simulation algorithm. Finally, we comment on the results and on future possible applications of the method.
Keywords: Mathematics, Ph.D.; Ph.D. Trinity College Dublin